Microbial ureolysis and ammonium oxidation in rice (Oryza sativa) rhizosphere: Impact of different fertilizers - KOUR, BABANPREET; PRUSTY, PRASANTA KUMAR; GAWDIYA, SANDEEP; SHIVAY, YASHBIR SINGH; RAMAKRISHNAN, BALASUBRAMANIAN (The Indian Journal of Agricultural Sciences, 2024)
Nitrogen is a crucial nutrient for rice (Oryza sativa L.) productivity, and chemical N fertilizers are often applied to enhance rice production. However, the response of soil microbial activity and corresponding functional genes to chemical fertilization remains unclear. The present study was carried out during rainy (kharif) seasons of 2019 and 2020 at the research farms of ICAR-Indian Agricultural Research Institute, New Delhi to study in the microbial responses to different concentration of nitrogen and fertilizers applied to the soil of rice fields. Study included a microcosmic experiment with 3 N concentrations (0, 10, and 100 mM), and treatment included were T1, RDF; T2, 50% N as urea and KNO3 at 75:25 with PK; T3, 50% N as urea and KNO3 at 75:25 with PK and ammonium oxidizing microbial consortium. Nitrogen addition at 10 and 100 mM increased urease activity by 19–26%, potential ammonium oxidation (PAO) by 16–49%, and ureC gene copies by 10–22%. Indeed, treated soils possessed 1.2 to 6.5 folds’ higher copies of archaeal- and bacterial amoA. In the field experiments, the rhizosphere of T1 showed the highest urease and PAO activities while having the lowest activity of ammonification. The abundance of ureC, archaeal-, and bacterial amoA genes ranged from 2.9×106 to 2.0×107, 4.6×103 to 2.4×104, and 2.3 to 9.4×106 copies/g soil, respectively. The ureC gene copies were more abundant in T1, while archaeal and bacterial amoA genes exhibited the highest copies in T3. Urease activity and ureC copies were highest during the vegetative stage, while PAO, and archaeal- and bacterial amoA gene copies were enriched during the flowering stage. The gene abundance and associated enzymatic activities showed a strong correlation, implying that structural changes in the microbial community due to different combinations of fertilizers might alter the nutrient turnover in soil. Our results showed that N-fertilizers could significantly alter the structure and activities of microbial communities, and appropriate N fertilization is necessary for improving the sustainability of rice cultivation.